STUDENTS LEARNING PROBLEMS IN EARLY READING AND WRITING AT GRADE 1 OF ELEMENTARY SCHOOL - Rosmayasari Rosmayasari (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2021)
Characteristics of students who have learning difficulties are minimum IQ levels, tend to have lower academic self-esteem than able students, cannot be good listeners, think, speak, read and write, write spelling, and even calculate the calculation of natural mathematics. This research is a qualitative study with the participants of grade 1 students in an elementary school in Bandung. The focus of this research is on students' difficulty in reading and writing initially. The results of the study found a way to deal with students who have difficulty learning to read and write initially by connecting the initial knowledge students have with the material to be taught, structuring a comfortable environment for learning, using interesting resources, learning material and media, provide lessons for improvement or improvement, provide repetition of material or enrichment, provide learning motivation, and build good learning attitudes and habits. The involvement of parents in overcoming student learning difficulties is to be able to establish communication with class teachers to find out their children's learning development, provide free time with children to discuss lessons that have been given at school, provide learning facilities, understand children's learning difficulties and provide guidance, and provide motivation in learning.